Dilema Profesionalisme Guru di Era Digital: Studi Pustaka tentang Tantangan Implementasi Kode Etik - Manziz, Ilham; Najwa Kamila Zada; Lailatus Syifa Azzahro; Nur Khasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has significantly transformed educational practices and created new challenges for teachers in maintaining professionalism. This study aims to analyze the dilemma of teacher professionalism in the digital era, particularly in relation to the implementation of the professional code of ethics. This research employed a qualitative approach using a library research method by examining relevant books, scientific articles, journals, and other academic sources. Data were analyzed through content analysis to identify patterns, challenges, and adaptive strategies related to teacher professionalism in digital contexts. The findings reveal that teacher professionalism in the digital era is not solely determined by pedagogical competence and technological mastery, but also by the ability to internalize ethical values in both online and offline professional practices. Major challenges include blurred boundaries between personal and professional identities, oversharing behavior on social media, digital ethical dilemmas, and increasing social pressure in public digital spaces. Therefore, teachers are encouraged to strengthen self-regulation and digital literacy, while educational institutions need to establish contextual digital ethics policies. This study contributes to educational science by offering a conceptual framework for reinterpreting teacher professional ethics in the context of digital transformation.